Remarkable morphological features of taxonomic interest in the female genitalia of five Erythrogonia species (Hemiptera: Cicadomorpha: Cicadellidae) - Carvalho, Rachel A.; Mejdalani, Gabriel (Zootaxa, 2014)
The female genitalia of the Cicadellidae (leafhoppers) are usually considered more morphologically conservative (i.e., less variable) than the male genitalia at the generic and specific levels. However, various recent publications on the Cicadellinae (sharpshooters) have demonstrated the existence of useful characters in the female genitalia for the recognition of genera and species. Here we describe, illustrate, compare, and discuss peculiar processes, sclerites, and other features of the first pair of valvifers, sternite VIII, and ovipositor valvulae I and II of five species of the sharpshooter genus Erythrogonia (E. calva (Taschenberg, 1884), E. hertha Medler, 1963, E. phoenicea (Signoret, 1853), E. proterva Melichar, 1926, and E. sexguttata (Fabricius, 1803)). This genus includes currently the highest species diversity among the New World Cicadellinae, an agriculturally important subfamily. Comparative notes on other genera of the Cicadellini are added. In agreement with other recent publications, our results challenge the view that the morphology of the female genitalia is almost always conservative in the Cicadellidae.